Numerical investigation to determine the optimal tilt angle of single slope solar still during summer season - Uzair, Muhammad; Naqvi, Asad A.; Yousuf, Muhammad Uzair (TECCIENCIA, 2022)
Water, a basic human need can be purified by different techniques like membrane distillation, boiling and solar still. Among all types, solar still is considered to be the most economical and simpler one. In this study, the geometrical aspects of the solar still for Karachi by varying the tilt have been simulated. The study is conducted by varying the height and length of the solar still by keeping the constant glass surface area and by varying the height and length of the glass cover while keeping the constant basin area. The study is conducted between the time duration from 08:00 to 18:00 hours which is generally the sunshine duration for Karachi. The simulation results are verified with the experimental results which shows the good agreement with each other. For constant glass cover area, the maximum mass production of water has been observed at a tilt of 60°C while for constant basin area the maximum tilt is observed for 24.8° equal to the latitude of Karachi. For both the cases, the maximum temperature of water and glass and maximum mass production of water is observed at around 13:00 hours.